The Impact of Round Table Technique towards Students’ Writing Ability - Herlisya, Destia (International Journal Corner of Educational Research, 2022)
The objective of this research was to know whether there was influence using round table technique towards students’ writing ability. The writer used experimental method. In taking the sample of the research, the writer used cluster Random Sampling Technique. The writer took two classes as the sample, one class was experimental class who was taught by round table technique and the another class was control class who was taught by discussion technique. In collecting the data, the writer used the writing test. For analyzing the data, the writer used t_tes formula. Based on the calculation, there is significant influence of round table technique towards students’ writing ability at the tenth class of SMK Negeri 4 Bandar Lampung. The average score of students who learn through round table technique is higher than by using discussion technique. It can be shown from the result in experimental class (71.96) > control class (60.71). Based on the result of data analysis, It shown that t_test = 5,51 is higher than t_table. At the significant level 5% or 1%, it was found the significance 0.05 = 2.00 and significance 0.01 = 2.66. It means that t_test> t_table, therefore (H_0) is rejected and〖 (H〗_a) is accepted. It means that there is significant influence of Round Table Technique towards students’ writing ability at the tenth class of SMK Negeri 4 Bandar Lampung.